2023
DOI: 10.1021/acscatal.2c05540
|View full text |Cite
|
Sign up to set email alerts
|

How pH Affects the Oxygen Reduction Reactivity of Fe–N–C Materials

Abstract: While Fe–N–C materials exhibit great potential for catalyzing the oxygen reduction reaction (ORR), their activity origin, especially the significant activity difference in acidic and alkaline media, remains a long-standing conundrum hindering the development of such catalysts. Here, we show an unanticipated pH-dependent regulation mechanism in Fe–N–C materials via first-principles microkinetic computations that explicitly consider the pH, solvation, and electrode potential effects. We find that, under typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 66 publications
(120 reference statements)
0
35
0
Order By: Relevance
“…To date, metal-nitrogen-doped carbon (M-N x -C) single-atom electrocatalysts have emerged as promising materials in the ORR to replace the precious-metal-based catalysts because of their fascinating characteristics (good activity, low cost, maximum atomic utilization, tunable electronic structures, etc.). [9][10][11][12][13] However, many challenges still remain to improve the electrocatalytic performance of the single-atom catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, metal-nitrogen-doped carbon (M-N x -C) single-atom electrocatalysts have emerged as promising materials in the ORR to replace the precious-metal-based catalysts because of their fascinating characteristics (good activity, low cost, maximum atomic utilization, tunable electronic structures, etc.). [9][10][11][12][13] However, many challenges still remain to improve the electrocatalytic performance of the single-atom catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…To date, metal–nitrogen-doped carbon (M–N x –C) single-atom electrocatalysts have emerged as promising materials in the ORR to replace the precious-metal-based catalysts because of their fascinating characteristics (good activity, low cost, maximum atomic utilization, tunable electronic structures, etc .). 9–13 However, many challenges still remain to improve the electrocatalytic performance of the single-atom catalysts. Therefore, many research studies have been devoted to overcome these challenges, such as trying to break through the limitation of dimension on the catalytic activity, improving the density of the single atomic active sites, and preventing the aggregation of metal atoms during the calcination process of the catalyst precursor, and remarkable results have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…20 So far numerous TM-N-C (TM = Fe, Co, Ni, etc.) electrocatalysts have been experimentally synthesized in the past decade, [21][22][23][24][25] but a precise control of the coordination environment on the transition metal site in TM-N-C is still difficult due to the amorphous nature of the graphene matrix. Thus, porous defects, topological defects, substitution of coordination atoms and various coordination structures of the TM center may exist, which give a chance to computational chemists to dig out how these factors affect the catalytic performance of TM-N-C. Up to now the effect of N/C coordination on the ORR activity and mechanism has been extensively reported via simulation.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] The theoretical studies for ORR have mainly reported the Gibbs free energy (DG) of the main reaction intermediates such as H*, OH*, O*, OOH*, and OO* at zero net charge with the goal of predicting the limiting potential (4) and overpotential (h = 1.23 − 4). [25][26][27] In most calculations, the dependence of the Gibbs free energy of the intermediates is assumed to be linear in the applied potential (U) as:…”
Section: Introductionmentioning
confidence: 99%
“…17–24 The theoretical studies for ORR have mainly reported the Gibbs free energy (Δ G ) of the main reaction intermediates such as H*, OH*, O*, OOH*, and OO* at zero net charge with the goal of predicting the limiting potential ( φ ) and overpotential ( η = 1.23 − φ ). 25–27 In most calculations, the dependence of the Gibbs free energy of the intermediates is assumed to be linear in the applied potential ( U ) as:Δ G OH* ( U ) = Δ G OH* | at U =0 V − eU Δ G O* ( U ) = Δ G O* | at U =0 V − 2 eU Δ G OOH* ( U ) = Δ G OOH* | at U =0 V − 3 eU where e is the electron charge. 28–30 However, linear dependence is assumed and has been shown to be incorrect in some studies.…”
Section: Introductionmentioning
confidence: 99%